Synergistic Therapeutic Effects and Immunoregulatory Mechanism of Maxing Shigan Decoction Combined with Sijunzi Decoction on Viral Pneumonia in Mice - Huimin Huang; Huanhua Yang; Zurong Zhang; Yunlong Song; Li Li; Ke Li; Junjie Zhang; Xiaoyu Qi; Ying Wu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Influenza is defined in traditional Chinese medicine (TCM) as an epidemic febrile illness and is usually treated with herbal compound formulas under the guidance of the “Qu Xie and Fu Zheng” theories. Ma Xing Shi Gan Tang (MXSGD) is a prominent remedy for clearing heat and detoxifying toxins in the clinical treatment of influenza in TCM, playing the role of “Qu Xie.” Si Jun Zi Tang (SJZD) is recognized as one of the “Fu Zheng” formulas for strengthening the spleen and nourishing the stomach, with immunomodulatory effects. In this study, we followed the principles of “Qu Xie and Fu Zheng” to explore the effects of MXSGD combined with SJZD on viral pneumonia and its mechanism. Results showed that the couse of MXSGD and SJZD was effective in reducing the mortality rates and severity of lung pathology in lethally infected FM1 mice compared to the use of either drug alone. Moreover, further research demonstrated that the combined use suppressed TLRs and NLRP3 inflammatory signaling pathways at 4 dpi while promoting them at 7 dpi. At 10 dpi, there was a significant increase in CD11c+ and CD103+ DCs in the lungs. Together, SJZD improved the therapeutic effectiveness of MXSGD in treating influenza virus pneumonia than when used alone. MXSGD and SJZD exhibit synergistic effects in the treatment of influenza, as evidenced by the inhibition of TLR7 and NLRP3 inflammatory pathways early in the infection and facilitation of the response later. They also increase CD11c+ and CD103+ DC levels, as well as balancing Th1/Th2 cytokines.